Is Presepsin a Reliable Marker of Sepsis Diagnosis in Pediatric Intensive Care Unit? - Algebaly, Hebat-Allah; Fouad, Hala M.; Elkholy, Maha M.; Ibrahim, Sally K.; Riad, Nermin M. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Sepsis is a major challenge in emergency departments and intensive care units (ICUs). Sepsis also mimics or interacts with many other disorders causing high mortality and morbidity. There is no accurate biomarker or test to diagnose or predict sepsis. The treatment of sepsis is often based on the clinician’s experience. AIM: We conducted this study to analyze the serum level of presepsin in pediatric critical patients with SIRS, sepsis, severe sepsis, and septic shock. METHODS: The study included 58 children, 32 septic pediatric patients admitted to the Pediatric ICU (PICU) of Cairo University Teaching Hospital and 26 healthy children who served as a control group. The aim was to estimate the diagnostic accuracy of presepsin in predicting sepsis in PICU. We classified the patients into systemic inflammatory response syndrome, sepsis, severe sepsis, and septic shock according to the international consensus conference criteria. RESULTS: In our study, we detected a positive correlation between C-reactive protein and presepsin levels at day 1 and day 3 of admission and a negative correlation between hemoglobin and presepsin levels at day 1. However, we found no difference in the serum presepsin between the children who had sepsis and the healthy ones (at day 1 [p = 0.430) and at day 3 [p = 0.845]). We also found that serum levels of presepsin were not significantly increased with the increasing severity of sepsis despite the higher median values with increasing sepsis severity. CONCLUSIONS: It was noted that presepsin levels increased in anemic critical patients, whereas presepsin had no role in differentiating the septic critical patients from healthy children. However, its level increased with increasing severity of sepsis grade.